1998
DOI: 10.1002/(sici)1521-3757(19980202)110:3<327::aid-ange327>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Cyano-Gilman-Reagentien oder Cyanocuprate höherer Ordnung?15N-,6Li- und13C-NMR-spektroskopische Untersuchungen an BuCu(CN)Li und Bu2CuLi⋅LiCN

Abstract: 1 ist die Hauptkomponente, die nach der Reaktion von 2 Äquiv. RLi mit 1 Äquiv. CuCN erhalten wird; andere vorgeschlagene Strukturen konnten jetzt auf der Grundlage von 15N‐NMR‐spektroskopischen und theoretischen Untersuchungen ausgeschlossen werden. Demnach lassen sich die präparativ nützlichen Reagentien R2CuLi⋅LiCN als Cyano‐Gilman‐Reagentien auffassen und sind keine Cyanocuprate höherer Ordnung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
3
20
1
2
Order By: Relevance
“…With the aid of 13 C, 6 Li, and 15 N NMR data [153], Bertz was able to point out that cyanide was not attached to copper(I) in the Lipshutz mix, and started the controversy [154,155]. Physical measurements by Penner-Hahn [156] and Lipshutz [157], and theoretical studies by Snyder [158], Penner-Hahn, and Frenking [159] contributed much to the discussion.…”
Section: ð10:15þmentioning
confidence: 64%
See 1 more Smart Citation
“…With the aid of 13 C, 6 Li, and 15 N NMR data [153], Bertz was able to point out that cyanide was not attached to copper(I) in the Lipshutz mix, and started the controversy [154,155]. Physical measurements by Penner-Hahn [156] and Lipshutz [157], and theoretical studies by Snyder [158], Penner-Hahn, and Frenking [159] contributed much to the discussion.…”
Section: ð10:15þmentioning
confidence: 64%
“…Evidence along the same lines was found in sodium and potassium derivatives [162]. The consensus, therefore, after many years of studies, is that triply coordinated [Cu(CN)R 2 ] 2À is not a stable structure in ethereal solution [153,[163][164][165]. Despite this conclusion, the Lipshutz mixed reagent still remains the one of choice in many synthetic transformations, and the presence of a triply coordinated cuprate(I) dianion was recently indicated by 13 Ca 13 CN carbon coupling in cyanostannylvinylcuprate(I) dianion in a THF/ HMPA mixture [166].…”
Section: ð10:15þmentioning
confidence: 99%
“…[91] Lipshutz et al reported that reagents formed by addition of two equivalents of RLi to CuCN are higher yielding than the corresponding Gilman organocuprates (R 2 CuLi) or lower order cyanocuprates (RCu(CN)Li), and described it as R 2 Cu(CN)Li 2 to imply a tricoordinated structure. [72b, 92] With the aid of 13 C, 6 Li, and 15 N NMR data, [93,94] Bertz et al pointed out that cyanide is not attached to copper(i) in the Lipshutz mix, and started the controversy. [95] Physical measurements by Penner-Hahn and co-workers [96,97] and Lipshutz et al, [98] and theoretical studies by the groups of Snyder, [99] and PennerHahn and Frenking [97] contributed much to the discussion.…”
Section: Organocopper Chemistrymentioning
confidence: 99%
“…[18b] Auch in Lösungen von R 2 Cu(CN)Li 2 -Cupraten gibt es ja den meisten Ergebnissen zufolge keine Cu-CN-Bindungen. [3±6] Higher-order-Cyanocuprate R 2 Cu(CN)Li 2 , oder besser: Cyano-Gilman-Cuprate, [19] scheinen somit gegenüber normalen Gilman-Cupraten R 2 CuLi zumindest im Anionenteil keine besonderen Bindungsverhältnisse aufzuweisen. Es ist darauf hinzweisen, daû in Festkörperstrukturen von Gilman-Cupraten Li an R-Cu-R À gebunden ist, es sei denn, Li wird durch Kronenether komplexiert.…”
unclassified